Development of a Drag-and-Drop-Based Science E-Module Using the Problem Based Learning Model to Improve Junior High School Students' Scientific Literacy and Problem-Solving Skills - Ika Ritaningsih; Bramastia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to develop a science e-module that integrates drag-and-drop interactions with the Problem-Based Learning (PBL) model to improve scientific literacy and problem-solving skills among seventh-grade junior high school students studying ecosystem topics. The low science literacy achievement of Indonesian students in PISA surveys and the predominantly procedural nature of their problem-solving abilities serve as the primary background of this research. Development was carried out using the Research and Development (R&D) method with the 4D approach—Define, Design, Develop, and Disseminate—and the product's effectiveness was tested using a One-Group Pretest-Posttest Design involving 32 seventh-grade students at MTsN 2 Karanganyar. Instruments used included subject-matter and media expert validation sheets, science literacy and problem-solving skills tests, and a student response questionnaire; content validity was established using Aiken's V (0.85–0.90), and reliability using Cronbach's Alpha (0.81–0.88). Validation results showed that the e-module received feasibility scores of 87.4% from subject matter experts and 89.1% from media experts, placing it in the